(untitled) (Economics and region, 2022)
The article investigates the adaptation to the modern market of fast food restaurants, in particular the "Fast casual" format. It is established that the new format is something between the established and familiar formats. Since fast food establishments are divided into three main categories: "Fast food", "Casual dining", "Fine dining", it was determined that the studied format is something between fast food and a restaurant of the middle price segment. The main differences between "Fast casual" and "Fast food" format were also analyzed and identified: more stylish interior, reusable tableware, varied menu, fresh products. That is why the studied format also has features similar to fast food, such as: a small area of the premises for the provision of services, the absence of waiters, only a bartender who serves dishes, as well as fast service. It is investigated that to determine the target audience it is necessary to take into account: geographical, demographic, socio-economic and psychographic factors. The observation method revealed that the largest visitors of "Fast casual" establishments are people who like healthy and simple food. According to observations, these are mainly office workers. Fast casual establishments are based on the fact that food in such establishments is prepared very quickly and is inexpensive. High table turnover is important for this format, because it is due to the large number of visitors that such an institution can be successful and profitable. It is determined that with the change of formats come new trends and technologies, which also positively affects the development of the industry as a whole and each individual institution. The attractiveness of the format and the success of the philosophy of quality food are becoming an ideology for many new brands in the industry. The fast food segment is in demand, so with the right concept, the business will stay afloat even in times of crisis and during martial law, when people are trying to save on everything, because it primarily affected expensive establishments and cafes, bars of the middle segment.